Effectiveness of Group Therapy Based on Acceptance and Commitment on Social and Health Adjustment of Nursing Students - Layla Noori; Amene Moradi Shakib; Elmira Ezazi Bojnourdi; Fakhteh Adib; Jamal Ashoori (Hamadan University of Medical Sciences, 2018)
Introduction: University students have a lot of problems in the field of adjustment especially social and health adjustment. Therefore, present research aimed to investigate the effectiveness of group therapy based on acceptance and commitment on social and emotional adjustment of nursing students. Methods: This research was carried out as a semi-experimental, with a pre-test and post-test design. The statistical population included all nursing students of Islamic Azad University of Pishva branch in 2015-16 academic year. 40 nurses were selected by voluntary sampling method and randomly assigned to two equal groups. The experimental group experienced 8 sessions of 90 minutes of education by group therapy based on acceptance and commitment. Groups completed the dimensions of social and health adjustment of Bell's adjustment questionnaire. Data were analyzed using SPSS19 and by multivariate analysis of covariance method. Results: The findings showed there was a significant difference between experimental and control groups in the social and health adjustment. In the other words, group therapy based on acceptance and commitment significantly led to improve the social and health adjustment of nursing students (P≤0/05). Conclusion: The results are due to the importance of group therapy based on acceptance and commitment on increasing social and health adjustment of nursing students. Therefore, it is suggested that counselors and therapists improve the dimension of adjustment especially social and health adjustment using group therapies based on acceptance and commitment.